2006
DOI: 10.1002/ar.a.20359
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ultrastructure of cortical and retinal terminals in the rat superior colliculus

Abstract: We compared the ultrastructure and synaptic targets of terminals of cortical or retinal origin in the stratum griseum superficiale and stratum opticum of the rat superior colliculus. Following injections of biotinylated dextran amine into cortical area 17, corticotectal axons were labeled by anterograde transport. Corticotectal axons were of relatively small caliber with infrequent small varicosities. At the ultrastructural level, corticotectal terminals were observed to be small profiles (0.44 Ϯ 0.27 m 2 ) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The ultrastructure of V1 corticotectal terminals and their postsynaptic targets in the mouse are remarkably similar to those of our previous study of V1 corticotectal terminals in the rat (Boka et al, ). In both species, corticotectal terminals are restricted to the SGS and SO and are small terminals (mouse 0.38 ± 0.21 μm 2 ; rat 0.44 ± 0.27 μm 2 ) that contain densely packed round vesicles and contact small caliber dendrites (mouse 0.31 ± 0.21 μm 2 ; rat 0.51 ± 0.69 μm 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…The ultrastructure of V1 corticotectal terminals and their postsynaptic targets in the mouse are remarkably similar to those of our previous study of V1 corticotectal terminals in the rat (Boka et al, ). In both species, corticotectal terminals are restricted to the SGS and SO and are small terminals (mouse 0.38 ± 0.21 μm 2 ; rat 0.44 ± 0.27 μm 2 ) that contain densely packed round vesicles and contact small caliber dendrites (mouse 0.31 ± 0.21 μm 2 ; rat 0.51 ± 0.69 μm 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…This could be supported by the fact that both types of sSC neurons receive glutamatergic inputs from the retina and the V1 (Boka et al, 2006), as well as GABAergic inputs from local interneurons (Endo et al, 2005;Kaneda et al, 2008). Our juxtacellular labelings showed that half of the labeled cells were putative excitatory neurons (4 WFV, 2 NFV, and 3 marginal cells out of 18 labeled neurons, Fig.…”
supporting
confidence: 59%
“…In addition, due to the close relationship of the GABA shunt and Krebs cycle, GABA is prone to be accumulated in the mitochondria, but this is again more prominent in cells that utilized GABA as a neurotransmitter (Gibson and Dianel 2007). Previous studies have used retinotectal or corticothalamic terminals known to be GABA negative to establish baseline values (Mize and Butler 1996; Patel and Bickford 1997; Boka et al 2006). Because we did not have that option, in that corticotectal terminals in SGI cannot be specified on ultrastructural grounds, we measured the gold particle density over myelin sheaths, which should not be GABA + , for use as a baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of axonal terminals in the SC has been studied in rat (Boka et al 2006), cat (Norita 1980; Behan et al 1987) and monkey (Mize et al 1991). Using cats, Norita (1980) divided the terminals in the neuropil of the deep SC into seven categories, based on the shape of their vesicles and their postsynaptic profiles.…”
Section: Discussionmentioning
confidence: 99%